JURIDICAL ANALYSIS OF HANDLING VICTIMS OF NARCOTICS ABUSE THROUGH REHABILITATION IN A LAW ENFORCEMENT PERSPECTIVE (RESEARCH STUDY AT THE NATIONAL NARCOTICS AGENCY RIAU ISLANDS PROVINCE) - Faozatulo Sadawa; Fadlan; Soerya Respationo; Erniyanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The practice of rehabilitation for narcotics abusers is still not in accordance with existing laws and regulations, namely that existing regulations are supposed to rehabilitate users who abuse narcotics, but this provision is never implemented, more perpetrators/victims are convicted than rehabilitated. Bearing in mind that Articles 56, 57, 58, 59 concerning Narcotics require that narcotics addicts and victims of narcotics abuse must undergo medical rehabilitation and social rehabilitation, so that narcotics abusers do not experience narcotics addiction again, both mentally and socially. The results of the research found that the Riu Islands Province National Narcotics Agency (BNN) carried out rehabilitation efforts according to applicable regulations, namely that there were still many addicts who refused to be isolated in a rehabilitation center. This happens because most narcotics addicts consider life in rehabilitation to be suffering for those who are still in the addiction stage, especially when going through a state of withdrawal. It turns out that the addict has experienced a semi-insane condition (dual diagnosis) or has experienced a serious illness that requires special medical treatment.